The social network - Reznor, Trent; Ross, Atticus, 1968- (Sony Pictures Home Entertainment, 2011)
On a fall night in 2003, Harvard undergrad and computer programming genius Mark Zuckerberg sits down at his computer and heatedly begins working on a new idea. In a fury of blogging and programming, what begins in his dorm room soon becomes a global social network and a revolution in communication. A mere six years and 500 million friends later, Zuckerberg is the youngest billionaire in history, but for this entrepreneur, success leads to both personal and legal complications.